DESIGN OF OPERATOR ASSIGNMENT FOR ASSEMBLY LINE OF EXCAVA 200 IN DIVISION OF HEAVY EQUIPMENT IN PT PINDAD (PERSERO) - APRILIANI NIM 13414043, CINDY
PT Pindad (Persero) is a state-owned enterprise (BUMN) company specializing in the production and sale of main weapon products (Alutsista) and commercial products. One of the commercial products produced by PT Pindad (Persero) is excavator. Excavator is just produced for 1 class which is class of 20 tons excavator with brand named Pindad Excava 200. Focus of this research is the assembly process of excavator in the Heavy Equipment Division. One of the problems that occured is the production target was not fullfield. The root cause of this problem is no operator assignment method in excavator assembly line. Therefore, it is necessary to design an operator assignment method that can be used to achieve the production target. This study proposes an assembly work assignment method using linear programming integer model. This model has an objective function to minimizes the cycle time by considering the operating tokime difference of each operator. Output of this model is assignment of task to operators and work stations. Computation is done by using LINGO software. Computation is modified with step by step computation to make a solution with more realistic time. The solution shows reduction of cycle time to 8,46 hours. This value is far less than current cycle time and takt time which is 39,5 and 31,2 hours respectively. Therefore, it cuts down 78,58% of current cycle time. There are 2 stations in A Zone for base assembly, 2 stations in B Zone for upper frame, and 3 stations in C Zone for the whole of excavator. This shows that proposed worker assignment result better outcome than existing condition as well as production target is fullfilled.